The XPO1 Inhibitor KPT-8602 Ameliorates Parkinson’s Disease by Inhibiting the NF-κB/NLRP3 Pathway - Liu, Shuhan; Wang, Shengxiang; Gu, Runze; Che, Na; Wang, Jing; Cheng, Jinbo; Yuan, Zengqiang; Cheng, Yong; Liao, Yajin (Frontiers in Pharmacology, 2022)
Exportin 1 (XPO1) is an important transport receptor that mediates the nuclear export of various proteins and RNA. KPT-8602 is a second-generation inhibitor of XPO1, demonstrating the lowest level of side effects, and is currently in clinical trials for the treatment of cancers. Previous studies suggest that several first-generation inhibitors of XPO1 demonstrate anti-inflammation activities, indicating the application of this drug in inflammation-related diseases. In this study, our results suggested the potent anti-inflammatory effect of KPT-8602 in vitro and in vivo. KPT-8602 inhibited the activation of the NF-κB pathway by blocking the phosphorylation and degradation of IκBα, and the priming of NLRP3. Importantly, the administration of KPT-8602 attenuated both lipopolysaccharide (LPS)-induced peripheral inflammation and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced neuroinflammation in vivo. In addition, the tissue damage was also ameliorated by KPT-8602, indicating that KPT-8602 could be used as a novel potential therapeutic agent for the treatment of inflammasome-related diseases such as Parkinson’s disease, through the regulation of the NF-κB signaling pathway and the NLRP3 inflammasome.